Board of Director Characteristics and CEO compensation: Empirical Evidence from Iran - Mahroo Irani; Mehdi Safari Gerayeli; Hasan Valiyan (Australasian Accounting, Business and Finance Journal, 2017)
This study aims to investigate the relationship between Board of Director characteristics and CEO compensation. This is semi-empirical study and statistical sample of research was based on 95 companies listed on the Tehran stock exchange from 2010 to 2014. Variables examined include the ratio of non-executive board members, CEO duality, ownership of institutional shareholders and managerial ownership as independent variables. Factors influencing CEO compensation were considered and the relationship between these variables was studied using multivariate regression. The findings indicate that there is a negative relationship between CEO compensation and managerial ownership. There is also a significant positive relationship between CEO compensation and CEO duality. However, there was no evidence for a significant relationship between ratios of non-executive board members and CEO compensation.
Keywords: CEO compensation; ratio of non-executive board members; CEO duality; ownership; institutional investors; managerial ownership.